Integrating Maternal and Child Health Into Climate Change: A Holistic Approach - Felix Amekpor; Waheed Sakariyau; Nathan Ezie Kengo; Nwodo Amarachukwu Sandra; Joseph Agyapong; Zakariya’u Dauda; Samuel Kwarteng; David Adeoye Adedokun; Gideon Darko (Public Health Reviews)
ObjectivesIn everyday language, climate change is an increase in the Earth’s average temperature. Climate change negatively affects life support systems, including air, food, water, shelter, and security, on which humans depend. This paper aims to holistically integrate maternal and child health into climate change.MethodsA narrative/literature review approach were adopted using papers sources from google scholar, research gate and web of science. About 10 papers was initially gathered and it was later scrutinized to 6.ResultsIt was discovered that, climate change negatively impacts food and water security, heat stress, extreme weather, and air pollution, with women and children most affected. The World Health Organization estimates 250,000 climate-related deaths annually by 2050, disproportionately affecting maternal and child health. Integrating climate and maternal health strategies could offer benefits, yet research on adapting to climate change’s effects on pregnancy outcomes is limited.ConclusionAddressing maternal and child health requires integrating health-focused strategies into environmental policies to reduce vulnerabilities to climate-related risks. A comprehensive approach can enhance resilience by improving healthcare access, education, and sustainable resource management, benefiting public health and environmental outcomes.